Role of Mechanically Alloyed Materials in Energy Storage and Automotive Applications - Khan, Hamaid Mahmood (Elsevier, 2024)
Due to global apprehensions surrounding environmental sustainability and the push for cleaner transportation, there has been a noticeable upsurge in the demand for effective energy storage systems and advanced materials in automotive applications (Suryanarayana & Al-Aqeeli, 2013; Suryanarayana et al., 2001). This has prompted a shift in the world’s attention towards the exploration of novel materials and innovative processing techniques capable of addressing the aforementioned challenges. p0015 Mechanically alloyed (MD) materials have emerged as a noteworthy category of materials receiving considerable recognition in energy storage and automotive applications (Neikov, 2019). Also referred to as ball-milled or mechanically milled materials, MD materials are produced using a solid-state powder processing technique that entails iterative cycles of cold welding, fracturing, and/or re-welding of powders within a high-energy ball mill. This causes the formation of distinctive nanocrystalline or amorphous structures, exhibiting properties that deviate from those observed in conventionally prepared materials (Wang & Zhang, 2023). p0020 Research findings have extensively outlined the exceptional attributes of MD materials when compared to their base counterparts. These attributes include enhanced mechanical strength, improved electrical and thermal conductivity, augmented surface area, and outstanding chemical stability (Dudina & Bokhonov, 2022). The ability to precisely control the composition, microstructure, and final morphology of MD materials, a structure with tailored properties can be obtained for specific applications.